Optimization Methods for the Cylinder Mouth Structure of Type IV On-board Hydrogen Storage Cylinder under Various Influencing Factors - Zhang Enhui; Wang Zhiqiang; Shi Xiaolong; Zhao Yangchun; Zhang Jiahui; Liu Tao; Wang Wenchao (E3S Web of Conferences, 2025)
This research investigates factors affecting the sealing reliability of Type IV hydrogen cylinder mouths under high-pressure fast-refueling conditions. A three-dimensional numerical analysis model and hydrogen energy conservation equation are developed to analyze sealing interface deformation incorporating static mechanics and computational fluid dynamics. Results demonstrate that internal pressure predominantly influences interface deformation, while external vibrations from road surfaces show negligible impact. Temperature emerges as the most critical factor: rising hydrogen temperatures increase thermal and total deformations, though their distribution patterns remain consistent. These findings provide theoretical guidance for optimizing hydrogen cylinder sealing designs and enhancing operational reliability. The research methodology integrates multiphysics simulations to evaluate combined mechanical-thermal effects, highlighting temperature management as a key consideration for maintaining seal integrity during rapid refueling cycles. And a control strategy to control the deformation generated during rapid filling of hydrogen storage bottles by temperature is proposed to improve the cooling efficiency.